Multiplex Real-Time Reverse-Transcription Polymerase Chain Reaction Assays for Diagnostic Testing of Severe Acute Respiratory Syndrome Coronavirus 2 and Seasonal Influenza Viruses: A Challenge of the Phase 3 Pandemic Setting. (20th October 2020) - Mancini, Fabiola; Barbanti, Fabrizio; Scaturro, Maria; Fontana, Stefano; Di Martino, Angela; Marsili, Giulia; Puzelli, Simona; Calzoletti, Laura; Facchini, Marzia; Di Mario, Giuseppina; Fabiani, Concetta; Bella, Antonino; et al.
Abstract: Background: Pandemic coronavirus disease 2019 (COVID-19) disease represents a challenge for healthcare structures. The molecular confirmation of samples from infected individuals is crucial and therefore guides public health decision making. Clusters and possibly increased diffuse transmission could occur in the context of the next influenza season. For this reason, a diagnostic test able to discriminate severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from influenza viruses is urgently needed. Methods: A multiplex real-time reverse-transcription polymerase chain reaction (PCR) assay was assessed using 1 laboratory protocol with different real-time PCR instruments. Overall, 1000 clinical samples (600 from samples SARS-CoV-2–infected patients, 200 samples from influenza-infected patients, and 200 negative samples) were analyzed. Results: The assay developed was able to detect and discriminate each virus target and to intercept coinfections. The limit of quantification of each assay ranged between 5 and 10 genomic copy numbers, with a cutoff value of 37.7 and 37.8 for influenza and SARS-CoV-2 viruses, respectively. Only 2 influenza coinfections were detected in COVID-19 samples. Conclusions: This study suggests that multiplex assay is a rapid, valid, and accurate method for the detection of SARS-CoV-2 and influenza viruses in clinical samples. The test may be an important diagnostic tool for both diagnostic and surveillance purposes during the seasonal influenza activity period. Abstract : A new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) wave may occur in fall/winter 2020 when the competitive influenza driver will be largely present. We report the development of a multiplex real-time polymerase chain reaction assay for detection of SARS-CoV-2 and seasonal influenza viruses.